2022
DOI: 10.1002/hsr2.727
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting successful sperm retrieval in men with nonobstructive Azoospermia: A single center perspective

Abstract: Predicting successful sperm retrieval is essential in counseling infertile men with Azoospermia.Objectives: To assess the predictors of successful sperm extraction in men with nonobstructive Azoospermia.Patients and Methods: A retrospective study included all patients with nonobstructive Azoospermia from January 2018 to May 2019. Subdivided into two groups, group I (negative sperm retrieval) and group II (positive sperm retrieval).Results: A total of 108 patients with a mean age of 36.8 ± 10 years were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Numerous studies have investigated the predictive potential of FSH [8] , [11] , [12] , [13] , [14] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . Given that FSH directly stimulates Sertoli cells within the testes to initiate spermatogenesis, the hypothesis emerged that FSH levels might serve as an indicator of testicular function and thus of the success of SR at mTESE [10] , [21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated the predictive potential of FSH [8] , [11] , [12] , [13] , [14] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . Given that FSH directly stimulates Sertoli cells within the testes to initiate spermatogenesis, the hypothesis emerged that FSH levels might serve as an indicator of testicular function and thus of the success of SR at mTESE [10] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results have emerged over time. For instance, Tsujimura et al [11] , [22] found that FSH was the most influential preoperative factor, together with InhB and total testosterone, in predicting SR. Aljubran et al [26] found that patient age and baseline serum FSH were independently associated with +SR among men with NOA undergoing mTESE. Conversely, more recent studies have found the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in andrology, when the current and ‘recently published’ mTESE literature is examined e.g. , when mTESE in NOA men is summarized [ 34 ]; or when factors predicting successful sperm retrieval among NOA men are assessed [ 13 ]; or when mTESE sperm extraction results of the first 100 patients are appraised [ 31 ]; or when the clinical experience of mTESE is evaluated [ 35 ], there is lack of acknowledgement of the need for skill building courses, such as the one described and evaluated here, to improve andrologists’ ability to perform mTESE optimally.…”
Section: Discussionmentioning
confidence: 99%
“…Further specialized knowledge is also required for patient-related and intra-operative predictors of mTESE success. A recent systematic review and meta-analysis as well as a range of studies found that age, testicular volume, follicle-stimulating hormone, luteinizing hormone, and testicular histopathology were valuable predictors of salvage mTESE extraction in NOA [ 12 13 ]. Furthermore, others proposed molecular biomarkers and noncoding RNAs in seminal plasma as predictors of sperm recovery [ 1 14 ].…”
Section: Introductionmentioning
confidence: 99%